ISOLASI KITOSAN DARI LIMBAH CANGKANG KEPITING BAKAU (Scylla serrata) DAN APLIKASINYA TERHADAP PENYERAPAN TRIGLISERIDA - Dali, Seniwati; Safitri, Nur Ramadhana Dewi; Fawwaz, Muammar (Jurnal Ilmiah As-Syifaa, 2016)
Chitosan is the result of deacetylation process from chitin which it can be found on Crustacean outer shell such as crabs. Chitosan can bind fat if it was consumed by human. The fat-binding ability of chitosan depends on the deacetylation degree. The research have been made into two phases. The first phase, chitosan was made from crab shell using NaOH. The deacetylation degree from chitosan that was made from the earlier process was analyzed with FTIR. The deacetylation degree result of the research was 59.39% using NaOH 50%. The second phase was the process of adsorbing triglycerides using chitosan in 10, 30, 45, and 60 minutes which was analyzed using spectrophotometer UV-Vis. The result of this research showed that the optimum triglycerides with 0.5, 1, 3 gram of chitosan was 2.99%, 3.14%, and 3.36%.